Дослідження впливу швидкості пресування на фізичну щільність брикетів із різнотипної біомаси - Кувачов, Володимир Петрович; Червоткіна, Олександра Олександрівна; Kuvachov, Volodymyr; Chervotkina, Oleksandra (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Робота зосереджена на експериментальному аналізі динамічного впливу швидкості пресування на фізичну щільність брикетів, виготовлених із трьох технологічно відмінних видів біомаси: лушпиння соняшнику, соломи та деревної тирси. Дослідження є актуальним для вдосконалення кінетики ущільнення різнорідної сировини. Кількісно встановлено нелінійну залежність щільності від швидкості пресування, підтверджено, що раціональний режим є критичним для якості. Максимальні значення щільності для всіх матеріалів досягнуто в діапазоні 10–12 мм/с, що свідчить про ідеальний час для термопластичної консолідації. Відхилення в бік низької швидкості спричиняє локальне термічне перенапруження й деструкцію зв’язувальних компонентів, а надмірне зростання швидкості призводить до збільшення пружної післядії та падіння щільності через недостатність часу на релаксацію. Отримані результати забезпечують наукову основу для диференційованого встановлення раціональних швидкісних режимів у промисловому брикетуванні. /// EN: This work focuses on the experimental analysis of the dynamic influence of pressing speed on the formation and final physical density of briquettes made from three technologically different types of biomass: sunflower husks, straw, and wood sawdust. The research is relevant for improving the kinetics of compacting heterogeneous raw materials and increasing the overall efficiency of production processes, taking into account the unique chemical composition of each material. A nonlinear dependence of density on pressing speed has been quantitatively established, confirming that the optimal speed regime is a critical determining parameter for the quality of the final product. The maximum density values for all materials studied were achieved in a narrow range of 10–12 mm/s, indicating the achievement of the ideal time required for complete thermoplastic consolidation and effective air removal (degassing). A detailed analysis of deviations revealed that movement towards a low speed of less than 5 mm/s causes local thermal overstressing of the material. Prolonged contact with the matrix leads to excessive friction, causing destruction of the binding components (especially oil fractions in the husk) and intense steam formation, which creates internal counter pressure, significantly reducing the final density. On the other hand, an excessive increase in speed of more than 15 mm/s leads to a critical drop in density and an increase in the elastic aftereffect coefficient due to insufficient time to complete viscoelastic relaxation and the formation of strong interparticle bonds. The results obtained provide a scientific basis for the differentiated establishment of rational speed regimes in industrial briquetting, which will minimize energy costs, reduce equipment wear, and ensure consistently high quality of the final biofuel. This increases the economic feasibility of biomass processing.
Study of the effect of pressing speed on the physical density of briquettes made from different types of biomass
Keywords: щільність брикету; сировина; лігнін; швидкість пресування; температура; briquette density; raw materials; lignin; pressing speed; temperature